Pengaruh Struktur Modal, Ukuran Perusahaan, Dan Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus Perusahaan Otomotif yang Terdaftar pada BEI Tahun 2012-2015) - Rahmatika, Lutfi Rizky, Dr. Syamsudin, MM (2017)
The company aims at the welfare of shareholders by increasing the value of the company. The company's high value indicates higher shareholder wealth. This study aims to analyze the influence of Capital Structure, Company Size, Profitability Against Corporate Values measured with Price Book Value. The population of this research is the automotive company listed on the Indonesia Stock Exchange in the year 2012 to 2015. The research method of sampling with purposive sampling method, with some predetermined criteria, the number of samples is as much as nine automotive companies. The research data is secondary data obtained from the Indonesia Stock Exchange (IDX) and the Annual Report 2012 to 2015. Analysis of the data used in this research is descriptive statistics test, classic assumption test and to test hypotheses using multiple regression analysis and path analysis with using SPSS 24. Based on the research of capital structure sifnifikan no positive effect on the value of the company, company size is not significant positive effect on the value, while profitability has a significant influence on the value of the company. Taken together these studies conclude capital structure, company size and profitability of significant positive effect on firm value. Suggestions from this study in determining the capital structure to use debt allowed where they provide more benefits, then the additional debt would still be allowed as a source of funding in the short and long term, so as to enhance shareholder value. While the effect on the profitability of the company's value.